PENGARUH PENYUPLEMENAN Spirulina DALAM PAKAN TERHADAP HEMATOLOGIS IKAN NILEM (Osteochilus hasselti C.V.) EFFECT OF SUPPLEMENTED Spirulina IN DIET ON NILEM FISH (Osteochilus hasselti C.V.) HAEMATOLOGYS - Ida Simanjuntak, Sorta Basar; Yuwono, Edy; Rachmawati, Farida Nur (Pembangunan Pedesaan, 2006)
The aim of this research was to know the effect of supplemented Spirulina in diet on nilem fish haematologys and to obtain the best dose. Pre-treated fishes were acclimated to the laboratory environment for 10 days then allocated randomly into 4 treatment groups. Each group consisted of three aquaria containing 100 L of water equipped with recirculatory system, 12 fishes were allocated into each aquarium. Fish in group A served as control given pellet without Spirulina. Fishes in groups B, C, and D were given pellet supplemented with 2, 4, and 6 g.kg-1 Spirulina, respectively, given daily at 07.30 and 16.00 at 5% of body weight. The results showed that haematologys profile on the nilem fish was affected by Spirulina. This was indicated by increasing erythrocyte counts, total leucocyte, and haemoglobin level as well as haematocrite value. Supplement with 4 g.kg-1 Spirulina was the best dose.